Harmful Stress-Related Couple Processes During the COVID-19 Pandemic and Lockdown: A Longitudinal Dyadic Perspective - Galdiolo, Sarah; Culot, Stéphanie; Delannoy, Pauline; Mauroy, Anthony; Laforgue, Florine; Gaugue, Justine (Frontiers in Psychology, 2022)
In March 2020, the WHO declared the disease caused by SARS-CoV-2 coronavirus “pandemic”. To reduce the risk of contamination, many countries have ordered a lockdown characterized by social distancing and restrictive isolation measures. While the lockdown has proven to be quite effective in terms of physical health, little is known about its impact on couple satisfaction in a dyadic perspective. The current research was a 4-waves longitudinal study (i.e., from March to July 2020) with the objective to examine the trajectory of couple satisfaction during the lockdown with a dyadic perspective (N = 108 couples), including the presence (or absence) of children, the number of hours spent together, and the duration of the relationship as time-invariant predictors and the partner’s couple satisfaction trajectory as a time-varying covariate. Results showed positive intraindividual changes in couple satisfaction during the lockdown, especially an increase in partners’ effectiveness for resolving couple conflicts and a decrease in partners’ aggressiveness. Partners had also perceived the influence of the lockdown as more and more positive over time on couple and family functioning. Finally, the couple satisfaction of both partners changed in tandem during the lockdown: The perception of the couple relationship seems to similarly evolve between partners.